1997
DOI: 10.1111/j.1365-2044.1997.240-az0374.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the next of kins' estimates of critically ill patients' quality of life

Abstract: SummaryThe aim of this study was to determine the reliability and validity of relatives' assessment of patients' quality of life and to measure the agreement between patients' and relatives' responses to the Short Form 36 quality of life questionnaire, at discharge from and 6 months following intensive care treatment. Ninety-nine patient-relative pairs were studied. Reliability was quantified by using measures of internal consistency (Cronbach's alpha and correlation coefficients) and reliability coefficients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 8 publications
3
76
0
1
Order By: Relevance
“…This study detected a trend towards negative proxy bias, but numbers were small (only 41 patient/lay proxy pairs were used), and the authors concluded that 'these preliminary findings need replication'. Finally, an inspection of the data published by Rogers et al [34] on patient/next-of-kin agreement in intensive care survivors appears to show a statistically significant negative proxy bias for 5 of the 8 SF-36 dimensions, although for the Mental Health dimension, a positive bias appears to be present.…”
Section: Discussionmentioning
confidence: 99%
“…This study detected a trend towards negative proxy bias, but numbers were small (only 41 patient/lay proxy pairs were used), and the authors concluded that 'these preliminary findings need replication'. Finally, an inspection of the data published by Rogers et al [34] on patient/next-of-kin agreement in intensive care survivors appears to show a statistically significant negative proxy bias for 5 of the 8 SF-36 dimensions, although for the Mental Health dimension, a positive bias appears to be present.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall reliability of the score is diminished under these circumstances, the physical score has been shown to be correlated with the actual patient answers. 24 Thus, the small number of families who answered the SIP score, especially the psychological part of the SIP score, may have altered the overall score. This most likely would bias the study toward a poorer outcome, because many families overestimate the psychological distress of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that a QOL questionnaire should be suitable to be completed by a close family member when the patient cannot respond [11]. Nevertheless, a QOL questionnaire should investigate the patient's personal perception of quality of life (as perceived quality of life of QOL-IT and emotional state of QOL-SP) [18], but relatives have been reported to be able to give a good assessment only of functional aspects of quality of life [19]. If we had interviewed relatives of comatose or confused patients, therefore, we could have introduced a bias.…”
Section: Discussionmentioning
confidence: 99%